2013
DOI: 10.1186/1472-6882-13-182
|View full text |Cite
|
Sign up to set email alerts
|

Antileptospiral activity of xanthones from Garcinia mangostanaand synergy of gamma-mangostin with penicillin G

Abstract: BackgroundLeptospirosis, one of the most widespread zoonotic infectious diseases worldwide, is caused by spirochetes bacteria of the genus Leptospira. The present study examined inhibitory activity of purified xanthones and crude extracts from Garcinia mangostana against both non-pathogenic and pathogenic leptospira. Synergy between γ-mangostin and penicillin G against leptospires was also determined.MethodsMinimal inhibitory concentrations (MIC) of crude extracts and purified xanthones from G. mangostana and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…All four crude extracts had greater MICs ranging from 200 to ≥ 800 µg/ml. The anti-leptospiral activity of five purified xanthones was variable in the range of 100 to ≥ 200 µg/ml (Seesom, et al, 2013). The above finding is in agreement with the present study that for PAE 20 to ≥ 160 µg/ml is giving 50 to 100% inhibition respectively.…”
Section: Discussionsupporting
confidence: 81%
“…All four crude extracts had greater MICs ranging from 200 to ≥ 800 µg/ml. The anti-leptospiral activity of five purified xanthones was variable in the range of 100 to ≥ 200 µg/ml (Seesom, et al, 2013). The above finding is in agreement with the present study that for PAE 20 to ≥ 160 µg/ml is giving 50 to 100% inhibition respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Swertia species have also been investigated for the presence of essential elements [105][106][107]. Xanthones have been reported to display hepatoprotective, antimicrobial, anticarcinogenic, antileprosy, antioxidant, anticholinergic, mutagenicity [108,109], and radioprotective effect [110], immunomodulatory effect [111], antibone resorption [112], and antiparasitic effects [113], neuraminidase inhibitory [114], antimalarial [115], anticomplement [116], antifungal and algicidal [117], and anti-HIV activity [118], and cardioprotective, antitumoral, antibacterial, antidiabetes, antihyperlipidemic, antiatherogenic, immunomodulator, anti-inflammatory, antiulcer, antiviral, antifungal [119], antidiabetic, hypolipidemic [120], analgesic, antiasthmatic, antihistaminic, antiamoebic, diuretic, antidiarrheal, larvicidal, ovicidal, antiprotozoal, antileptospiral, anti-TMV, and anticancer activities [121][122][123][124]. Xanthones from S. mussotii were evaluated for their anti-hepatitis B virus activity on HepG 2.2.15 cells line; they exhibited significant activity inhibiting hepatitis B virus DNA replication with IC 50 values from 0.01 mM to 0.13 mM [125].…”
Section: Biological Activities Of Xanthonesmentioning
confidence: 99%
“…Alpha mangostin damage the integrity of the cytoplasmic membrane of bacteria rapidly, causing damage in intracellular component bacteria and cause the bacteria to die. A study conducted by Seesom et al (2013) stated that α-mangostin has the potential to inhibit the growth of Mycobacterium tuberculosis. Other studies on antibacterial activity of mangostin was coducted by Zou et al (2013) stating that the test on the effect of mangostin against Pseudomonas aeruginosa and Klebsiella pneumoniae resulted in MIC of 40-50 µg/mL.…”
Section: Statistic Analysismentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of alpha-mangostin against Gram + especially Staphylococcus aureus, Leptospira and Mycobacterium tuberculosis (Seesom et al, 2013). Another study of Bhat and Daihan (2013) showed a moderate susceptibility of bacteria to xanthones in the extract of Garcinia mangostana L. is Staphylococcus aureus, Streptococcus pyogenes, Bacilus subtilis and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%